2022
DOI: 10.3390/molecules27041242
|View full text |Cite
|
Sign up to set email alerts
|

Practical Synthesis of Phosphinic Dipeptides by Tandem Esterification of Aminophosphinic and Acrylic Acids under Silylating Conditions

Abstract: In this report, a synthetic protocol for the preparation of phosphinic dipeptides of type 5 is presented. These compounds serve as valuable building blocks for the development of highly potent phosphinopeptidic inhibitors of medicinally relevant Zn-metalloproteases and aspartyl proteases. The proposed method is based on the tandem esterification of α-aminophosphinic and acrylic acids under silylating conditions in order to subsequently participate in a P-Michael reaction. The scope of the transformation was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Another major concern that must be taken under consideration is that optimization opportunities strongly depend on synthetic advances in the field, ,,, as highlighted by the application of combinatorial chemistry principles in the discovery of selective inhibitors of several Zn-metalloproteases ,,, or the successful preparation of capricious sequences which allowed the synthesis of RXPA380 , or inhibitors of aminopeptidase A. , Finally, the transformation of phosphinic inhibitors of MMPs to molecular probes has set the basis for similar studies with other pharmacologically important Zn-metalloproteases, expanding the range of applications of this privileged class of tool compounds. Future development of novel, improved tool compounds or probes thereof will be largely accelerated by addressing unmet challenges such as stereoselective synthetic strategies, late-stage diversification approaches, or synthesis of unusual, conformationally constrained analogues. …”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Another major concern that must be taken under consideration is that optimization opportunities strongly depend on synthetic advances in the field, ,,, as highlighted by the application of combinatorial chemistry principles in the discovery of selective inhibitors of several Zn-metalloproteases ,,, or the successful preparation of capricious sequences which allowed the synthesis of RXPA380 , or inhibitors of aminopeptidase A. , Finally, the transformation of phosphinic inhibitors of MMPs to molecular probes has set the basis for similar studies with other pharmacologically important Zn-metalloproteases, expanding the range of applications of this privileged class of tool compounds. Future development of novel, improved tool compounds or probes thereof will be largely accelerated by addressing unmet challenges such as stereoselective synthetic strategies, late-stage diversification approaches, or synthesis of unusual, conformationally constrained analogues. …”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…A synthetic protocol for the preparation of novel phosphinic dipeptides was presented by Georgiadis and co-workers [ 2 ]. These compounds serve as valuable building blocks for developing highly potent phosphinopeptidic inhibitors of medicinally relevant Zn-metalloproteases and aspartyl proteases.…”
mentioning
confidence: 99%
“…We found that the use of a phenyl-isoxazole-substituted acrylic derivative leads to the respective PDI 5a with a 5.1:1 dr, while replacement of ethyl with benzyl ester further increases the observed dr to 6.0:1, as demonstrated in the case of PDI 5b . Moreover, we produced a common derivative from known PDI 4a and newly synthesized isoxazole PDI 5a , and after comparison by 31 P NMR, we confirmed that the S stereochemical configuration at position P 1 ′ is favored (see the Supporting Information), in accord with previous reports. , Strikingly, the dr for 5b was dramatically increased to 10:1 when CH 2 Cl 2 was replaced by a polar aprotic solvent (MeCN or DMF) and to 18:1 when the reaction mixture was stirred first at 4 °C for 24 h and then at room temperature for 48 h. Next, we evaluated the effect of a carboxylic ester moiety on the observed diastereoselectivity, as depicted in Scheme B. In general, benzyl type esters 5c – h were generated with improved diastereoselectivities in all cases compared to that of reference ester 5b (20–25:1 vs 18:1).…”
mentioning
confidence: 99%